Infection of Tick Cells and Bovine Erythrocytes with One Genotype of the Intracellular Ehrlichia Anaplasma marginale Excludes Infection with Other Genotypes - de la Fuente, José (American Society for Microbiology, 2002)
Anaplasma marginale, a tick-borne rickettsial pathogen of cattle, is endemic in several areas of the United States. Many geographic isolates of A. marginale that occur in the United States are characterized by the major surface protein 1a, which varies in sequence and molecular weight due to different numbers of tandem repeats of 28 or 29 amino acids. Recent studies (G. H. Palmer, F. R. Rurangirwa, and T. F. McElwain, J. Clin. Microbiol. 39:631-635, 2001) of an A. marginale-infected herd of cattle in an area of endemicity demonstrated that multiple msp1α genotypes were present but that only one genotype was found per individual bovine. These findings suggested that infection of cattle with other genotypes was excluded. The present study was undertaken to confirm the phenomenon of infection exclusion of A. marginale genotypes in infected bovine erythrocytes and cultured tick cells. Two tick-transmissible isolates of A. marginale, one from Virginia and one from Oklahoma, were used for these studies. In two separate trials, cattle inoculated with equal doses of the two isolates developed infection with only one genotype. Tick cell cultures inoculated with equal doses of the two isolates became infected with only the Virginia isolate of A. marginale. When cultures were inoculated with different ratios of the Oklahoma and Virginia isolates of A. marginale, the isolate inoculated in the higher ratio became established and excluded infection with the other. When cultures with established infections of one isolate were subsequently infected with the other, only the established isolate was detected. We documented infection exclusion during initial infection in cell culture by labeling each isolate with a different fluorescent dye. After 2 days in culture, only a single isolate was detected per cell by fluorescence microscopy. Finally, when Anaplasma ovis infections were established in cultures that were subsequently inoculated with the Virginia or Oklahoma isolate of A. marginale, A. marginale infection was excluded. These studies confirm that infection exclusion occurs with A. marginale in bovine erythrocytes and tick cells, resulting in the establishment of only one genotype, and appears to be the first report of infection exclusion for Anaplasma and Ehrlichia species.